Microplastics in indoor air and dust: characterization, risk factors, and health risks - Ainur Balqis, Radzi; Norhidayah, Abdull; Tay, Joo Hui; Okochi, Hiroshi; Shinohara, Ken-ichi (Springer, 2026)
Microplastics (MPs <5 mm) have become a growing concern in indoor environments, where their concentrations often exceed those outdoors. Familiar indoor sources include textiles, furniture, paints, and cleaning products, while factors such as ventilation type, occupancy level, and cleaning practices influence their abundance. This review synthesizes current findings on the occurrence, characterization, and risk factors of airborne and dust-borne MPs indoors in various indoor settings, and also based on continent and country income from high to low-income countries. Overall, airborne MP concentrations tend to be higher in lower-middle-income countries, particularly in Southeast Asia and South America, and are generally higher than in high-income regions. Advances in sampling and analytical techniques (including microscopy, FTIR, Raman spectroscopy, and pyrolysis-GC-MS) are discussed alongside the particles' physical and chemical properties. Evidence from toxicological studies demonstrates that inhalation, ingestion, and dermal exposure to MPs are linked to oxidative stress, inflammation, endocrine disruption, and organ-specific effects on the respiratory, digestive, reproductive, immune systems, and nervous systems. This review highlights the urgent need for harmonized monitoring protocols, comprehensive risk assessment, and effective mitigation strategies, such as improved cleaning, ventilation, and material substitution, to reduce exposure and safeguard human health in indoor environments.